Deciphering nifedipine in vivo delivery from modified release dosage forms: Identification of food effect - Ilić Marija; Kovačević Ivan; Parojčić Jelena (Acta Pharmaceutica)
With the increased reliance on in vitro dissolution testing as an indicator of in vivo drug behavior and the trend towards the in silico modeling of dosage form performance, the need for bioperformance dissolution methodology development has been enhanced. Determination of the in vivo drug delivery profile is essential for the bioperformance dissolution test development and in vitro/in vivo correlation modeling, as well as the understanding of absorption mechanisms. The aim of this study was to compare different methods in terms of their usefulness and applicability in deciphering in vivo delivery of nifedipine administered in modified release dosage forms. A detailed survey of publications on nifedipine pharmacokinetics was done and used to identify the magnitude of food effect. In vitro dissolution testing was performed under various experimental conditions. Obtained results indicate the potential for using the developed in silico model coupled with discriminative in vitro dissolution data for identification of the in vivo drug product behavior